Population-based Study of 24 Autoimmune Diseases Carried Out in a Brazilian Microregion - Dilceu Silveira Tolentino Júnior; Carla Meireles de Oliveira; Eliseu Miranda de Assis (Springer, 2019)
In Brazil, epidemiological data on autoimmune diseases are scarce due to the lack of a specific policy of attention to this group of diseases. This study aimed to estimate the general and relative prevalence of the diseases presented, as well as to know the sociodemographic profile of the identified cases. This cross-sectional study was conducted with an epidemiological survey of patients with confirmed diagnosis of autoimmune diseases from primary health care in the Aguas Formosas microregion, Minas Gerais, Brazil. We have included all new and old cases found of individuals of both sexes and all ages, including those who died and emigrated during this period. A total of 407 carriers and 24 different autoimmune diseases were identified. The prevalence of autoimmune diseases in this region was 673.6 cases per 100,000 inhabitants [95% confidence interval (CI): 609.8-742.4]. Highest prevalence was identified for Hashimoto's thyroiditis 140.6 cases per 100,000 (95% CI: 112.4-173.9), followed by vitiligo 132.4 cases per 100,000 (95% CI: 105.0-164.8), and rheumatoid arthritis 105.9 cases per 100,000 (95% CI: 81.6-135.3). The sex ratio was higher in females (69%), the most affected age group was over 60 years (30.5%), with greater predominance in the urban area (81.3%). Our data showed the general and relative prevalence of the identified diseases, allowing to know the sociodemographic profile of the identified cases and the epidemiological trend of these morbidities in a low-income Brazilian region.